2004
DOI: 10.1002/ejic.200400235
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Optical Properties and Theoretical Studies of Pt(P−P)(CN)2 with P−P = 1,2‐Bis(diphenylphosphanyl)benzene and 2,2′‐Bis(diphenylphosphanyl)‐1,1′‐binaphthyl − Luminescence from Metal‐to‐Ligand Charge Transfer and Intraligand States

Abstract: The complexes Pt II (P−P)(CN) 2 with P−P = 1,2-bis(diphenylphosphanyl)benzene (dppb) and 2,2Ј-bis(diphenylphosphanyl)-1,1Ј-binaphthyl (binap) were synthesised and characterised by elemental analysis, ESI MS and electronic spectroscopy. The structure of Pt(dppb)(CN) 2 was resolved by single-crystal X-ray diffraction. This compound consists of mononuclear Pt II complexes with an almost planar PtP 2 C 2 coordination. While both complexes are not luminescent in solution, they show an emission in the solid state un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…1) shows absorptions at k max = 340 (sh, e = 3400 M À1 cm À1 ), 318 (sh, 6250), 280 (sh, 13,200), 252 (sh, 30,000), 228 (sh, 56,500) and 207 (63,000) nm. The longwavelength portion of this spectrum with both shoulders at 340 and 318 nm shows the same pattern as the spectra of the binap complexes of Pt(II) and Au(I) [21,22]. The emission behavior of these complexes is also almost identical to that of Ag(binap)NO 3 which does not luminesce in solution but exhibits a bright green-yellow emission in the solid state at r.t. Vibrational features of the luminescence spectrum (Fig.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…1) shows absorptions at k max = 340 (sh, e = 3400 M À1 cm À1 ), 318 (sh, 6250), 280 (sh, 13,200), 252 (sh, 30,000), 228 (sh, 56,500) and 207 (63,000) nm. The longwavelength portion of this spectrum with both shoulders at 340 and 318 nm shows the same pattern as the spectra of the binap complexes of Pt(II) and Au(I) [21,22]. The emission behavior of these complexes is also almost identical to that of Ag(binap)NO 3 which does not luminesce in solution but exhibits a bright green-yellow emission in the solid state at r.t. Vibrational features of the luminescence spectrum (Fig.…”
supporting
confidence: 51%
“…Since the absorption and emission spectra of Ag(binap)NO 3 are very similar to those of Pt(binap)(CN) 2 [22] and Au 2 Cl 2 binap [21] it is concluded that the lowest and emissive excited state of the silver complex is also of the binap IL type. For the free ligand this phosphorescence occurs only at low temperatures (77 K) [23].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…For X = CN the LF states should be pushed up to very high energies owing to the large LF strength of cyanide [11]. Accordingly, low-energy IL or MLCT states were expected to determine the photoproperties of Pt II (C 8 H 8 )(CN) 2 in analogy to complexes of the type Pt II (L-L)(CN) 2 with L-L = 1,2-diimine [12] or bidentate phosphine [13].…”
mentioning
confidence: 99%